Modulational instability in two-component discrete media with cubic-quintic nonlinearity - Baizakov, Bakhtiyor B; Bouketir, Ahmed; Messikh, Azeddin; Umarov, Bakhram (American Physical Society, 2009)
The effect of cubic-quintic nonlinearity and associated intercomponent couplings on the modulational instability MI of plane-wave solutions of the two-component discrete nonlinear Schrödinger DNLS equation is considered. Conditions for the onset of MI are revealed and the growth rate of small perturbations is analytically derived. For the same set of initial parameters as equal amplitudes of plane waves and intercomponent coupling coefficients, the effect of quintic nonlinearity on MI is found to be essentially stronger than the effect of cubic nonlinearity. Analytical predictions are supported by numerical simulations of the underlying coupled cubic-quintic DNLS equation. Relevance of obtained results to dense Bose-Einstein condensates BECs in deep optical lattices, when three-body processes are essential, is discussed. In particular, the phase separation under the effect of MI in a two-component repulsive BEC loaded in a deep optical lattice is predicted and found in numerical simulations. Bimodal light propagation in waveguide arrays fabricated from optical materials with non-Kerr nonlinearity is discussed as another possible physical realization for the considered model.